2018
DOI: 10.1155/2018/8570986
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Intake among Premenopausal Women Living in Jeddah: Food Sources and Relationship to Demographic Factors and Bone Health

Abstract: Background Saudi women depend on food sources to maintain their serum 25(OH) D concentrations because covering by traditional clothing and time spent indoors limit their sun exposure. Little is known about vitamin D intake and its main food sources in Saudi Arabia. In addition, the association between vitamin D and calcium intake and bone mineral density (BMD) in young women is not well researched. Objectives To assess the adequacy of vitamin D intake among Saudi women as compared to the estimated average requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 39 publications
2
29
2
Order By: Relevance
“…Such a positive validation, as in the presented study, indicates that the validated Cro-VIDEO-FFQ questionnaire may be applied to assess the vitamin D intake in the Croatian young women population, which was previously indicated as necessary due to general high prevalence of vitamin D deficiency in a Croatian population [ 10 ] and due to the need to monitor the intake [ 17 ]. Moreover, the lack of vitamin D data in the Croatian food composition tables imposes such actions for the public health purposes.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Such a positive validation, as in the presented study, indicates that the validated Cro-VIDEO-FFQ questionnaire may be applied to assess the vitamin D intake in the Croatian young women population, which was previously indicated as necessary due to general high prevalence of vitamin D deficiency in a Croatian population [ 10 ] and due to the need to monitor the intake [ 17 ]. Moreover, the lack of vitamin D data in the Croatian food composition tables imposes such actions for the public health purposes.…”
Section: Discussionsupporting
confidence: 61%
“…In our study, the main sources of vitamin D for young women were fish products, meat products, eggs, and dairy products. At the same time, while other questionnaires were used, Bärebring et al [ 22 ] observed fish products, spread margarine, and dairy products (including fortified ones) mainly as vitamin D sources for Swedish young women population, while Zareef et al [ 17 ] observed dairy products (including fortified ones) and fish products as the less important for Saudi Arabian young women. The main difference in comparison with other populations is the role of meat products as a source of vitamin D in the Croatian population, although the general vitamin D content in meat products is rather low [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Young populations living in sunny areas like UAE, Saudi Arabia, and India have a high prevalence of VDD due to insufficient knowledge and practice of vitamin D and its health implications [9][10][11][12][13][14] . Especially female adolescents are in danger to develop osteoporosis in their later life due to their risky behavior of physical inactivity, sun-avoidance behavior, low intake of dairy products and poor diets 14,15 .…”
Section: -Hydroxyvitamin D [25(oh)d]mentioning
confidence: 99%